Children Go Online” di Indonesia, Apa dan Bagaimana? - Nurist Surayya (Jurnal Ilmiah Komunikasi Makna, 2015)
The high penetration of internetaccesses in Indonesia has impacted on media consumption among Indonesian children. Despite many potential upportunities, internet accesses among children also carry some risks of harm. Accordingly, it raisedconcerns, especially deal with childrenvulnerability of going online and their online safety protections. Thus, the requisite stepdeals with identifying risks and upportunities of children go online, especially about how do children access the internet.In the present article, we focus on illustrating how and what children do when go online. Based on survey toward 215 childrens age 6-12 years old with various demographic backgrounds, this study describes time accesses, platforms, online activities, sites and risks of Indonesian children go online.Keywords: Children,Go Online, Indonesia